The importance of pharmaceutical care in women during pregnancy (Research, Society and Development, 2020)
Pharmaceutical care is a relevant service to promote the rational drug use and pharmacotherapeutic success, due to the pharmacist's knowledge and accessibility. On this regard, there is a great relevance on providing this service to pregnant women, due to the possible maternal-fetal risks associated with some drugs. As well as pre-existing diseases and conditions for instance, arterial hypertension and gestational diabetes mellitus which require the use of pharmacological therapies and are of great relevance in Brazilian public health. Due to the high incidence and the complications they may cause, it is an opportune period for the pharmaceutical care to assist treatment adherence and consequently achieve therapeutic success. In this context, the aim of this study is to understand the importance of clinical pharmacists in the pharmacological care during pregnancy. A research was carried out in the databases Scielo, Google Scholar, PubMed and ScienceDirect databases, using the descriptors: risk categories; hypertension; diabetes mellitus; self-medication; pregnancy; nausea; vomiting; eclampsia and pharmaceutical assistance, all selected from DeCS in the languages: Portuguese and English. The importance of pharmaceutical care in pregnancy was evidenced through this study regarding not only the safety and adequate guidance to the use of drug therapies to reduce self-medication, but also the therapeutic adherence process through continuous and regular monitoring. Hence, contributing to the improvement of both maternal and fetal life quality by the pharmaceutical care that highlights whenever necessary the importance of correct treatment compliance and advises the need of therapeutic interventions. Therefore, this study has a unique relevance once it explained the pharmaceutical care importance for pregnant women. Furthermore, it collaborates for the development of plans and actions that aim to expose and conscientize the importance of the clinical pharmacist during this period.